A Meta-Analytic Literature Review on Organization-Level Drivers of Team Learning. (June 2020) - Nellen, Lydia C.; Gijselaers, Wim H.; Grohnert, Therese
Organizations have a marked interest in fostering team learning to manage performance and innovation. However, practitioners and researchers currently lack coherent knowledge on which drivers are effective at fostering team learning. Along with team learning, we also focus on the emergent states of psychological safety, shared cognition, team potency/efficacy, and cohesion, previously related to team learning. In this meta-analysis, we include 50 quantitative studies providing information on 4, 778 teams of professionals across manufacturing, product development, academic research and teaching, health care, and professional services. First, we find that team learning correlates positively, if moderately, with four organization-level drivers: top-level leadership, organizational culture, job resources, and organizational infrastructure. Second, two of these drivers also correlate robustly with team emergent states: organizational culture and job resources. These findings provide specific levers and estimates of relative influence to guide managerial practice and future research on team learning.